2019
DOI: 10.1186/s12889-018-6357-x
|View full text |Cite
|
Sign up to set email alerts
|

Offering HCV treatment to prisoners is an important opportunity: key principles based on policy and practice assessment in Europe

Abstract: BackgroundPrisoners have a high prevalence of hepatitis C virus (HCV) infection but may find it difficult to access healthcare services. This may be related to risk behaviour including history of injecting drugs and marginalisation related to problem drug use/ opioid use disorder (OUD). Direct-acting antiviral products with superior efficacy and safety compared to interferon-based regimens offer HCV cure. Many citizens in Europe have been treated, although few received therapy in prisons.MethodsAnalysis of pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 34 publications
0
28
0
1
Order By: Relevance
“…In the other 13 countries, the extent of HCV treatment was reported as available in more than half of all prisons, less than half of all prisons or unknown. Another study estimated the prison population in need of treatment in France, Germany, Italy, Spain and United Kingdom (England and Wales) to be between 6000 and 9000 in 2015 [ 39 ], representing 9.3 to 11.5% of the total prisons population in these countries highlighting a large treatment gap. More recent information from the EMCDDA indicate that HCV treatment in prisons is now available in 24 European countries, but data on coverage are lacking [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the other 13 countries, the extent of HCV treatment was reported as available in more than half of all prisons, less than half of all prisons or unknown. Another study estimated the prison population in need of treatment in France, Germany, Italy, Spain and United Kingdom (England and Wales) to be between 6000 and 9000 in 2015 [ 39 ], representing 9.3 to 11.5% of the total prisons population in these countries highlighting a large treatment gap. More recent information from the EMCDDA indicate that HCV treatment in prisons is now available in 24 European countries, but data on coverage are lacking [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…El tratamiento con los actuales AAD para la HCc ha demostrado generar beneficios a nivel epidemiológico, clínico y económico 19,20 . Por consiguiente, la principal herramienta para eliminar la infección por VHC debería ser dar acceso a terapias con AAD sin limitaciones, aunque esta herramienta pueda y deba complementarse con otras de tipo preventivo y educativo, como ha sido recomendado por expertos del ámbito penitenciario en alguna reciente publicación 31 . Sin embargo, este acceso está restringido en muchos países 32 , y todavía más en presos 33 , básicamente por motivos económicos 34,35 .…”
Section: Discussionunclassified
“…Treatment with current DAAs for CHC has demonstrated that they generate benefits at epidemiological, clinical and economic levels 19 - 20 . Therefore, the main strategy for eliminating HCV infection recommended by prison experts in a recent publication 31 . However, access to this treatment is access to this is restricted in many countries 32 and even more so to even more in prisoners 33 , essentially for economic reasons 34 - 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies on evidence of effectiveness of these measures inside prison are limited (10,52,53). However, doubts are raised on the need to have evidence of effectiveness for implementing health interventions inside prison when those interventions have been already proved to be effective in the community (53)(54)(55)(56)(57). Furthermore equivalence and continuity of care are key principles for conducting health and social interventions in prisons (53,(58)(59)(60) and intervening on people in prison may have a larger positive impact on public health in the community (53,61,62).…”
Section: Introductionmentioning
confidence: 99%